2023
DOI: 10.1021/acs.jpca.2c08821
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Vertical Ionization Potentials from DFT via a Graph-Network-Based Delta Machine Learning Model Incorporating Electronic Descriptors

Abstract: While accurate wave function theories like CCSD­(T) are capable of modeling molecular chemical processes, the associated steep computational scaling renders them intractable for treating large systems or extensive databases. In contrast, density functional theory (DFT) is much more computationally feasible yet often fails to quantitatively describe electronic changes in chemical processes. Herein, we report an efficient delta machine learning (ΔML) model that builds on the Connectivity-Based Hierarchy (CBH) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Figure 12 shows a bar plot of the 10 most important CBH fragments, ranked by their feature permutation score. It is interesting to note the prevalence of fragments featuring amines (13,36,16,72,25,41), alcohols, and carboxylic acids (2,10,25). This aligns with our expectations since N and O are the most abundant heavy atoms (excluding carbon) in the data set (see Figure 3).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 12 shows a bar plot of the 10 most important CBH fragments, ranked by their feature permutation score. It is interesting to note the prevalence of fragments featuring amines (13,36,16,72,25,41), alcohols, and carboxylic acids (2,10,25). This aligns with our expectations since N and O are the most abundant heavy atoms (excluding carbon) in the data set (see Figure 3).…”
Section: Resultssupporting
confidence: 87%
“…To address this demand, several recent studies have demonstrated the successful integration of quantum mechanical (QM) calculations and machine learning (ML) techniques for highly accurate physicochemical property prediction. The adaptation of ML as a viable tool in the quantum chemist’s toolbox has led to numerous applications in materials discovery, catalysis, drug design, etc. When it comes to p K a prediction, one QM/ML model by Hunt et al used semiempirical features along with radial basis functions to obtain commendable performance on the SAMPL6 and Jensen data sets . Similarly, Lawler et al used features derived from DFT with a kernel ridge regression model to achieve a low mean absolute error (MAE) of 0.60 on oxoacids.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we pointed out earlier that the aromatic units (e.g., phenyl groups) were left intact in our p K a studies . In a more recent study, we obtained slightly better performance from coarse-graining other functional groups such as nitro groups, sulfoxides, nitriles, etc . This is an active topic of ongoing research.…”
Section: Other Applications and Future Prospectsmentioning
confidence: 59%
“…They demonstrate the effectiveness of their method compared to other approaches using L- and M-edge XAS for transition metal and actinide compounds. In the machine-learning (ML) domain, coupled-cluster-level accuracy from DFT may be possible using well-designed ML models, according to work by Maier, Collins, and Raghavachari at Indiana University . Using an efficient Δ-ML model with a systematic molecular fragmentation approach, they report such accuracy for vertical ionization potentials.…”
Section: New Algorithms In Quantum Chemistrymentioning
confidence: 99%